Justice, Democracy and the Right to Justification Rainer Forst in Dialogue - Forst, Rainer (Critical Powers, 2014)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Over the past 15 years, Rainer Forst has developed a fundamental research programme within the tradition of Frankfurt School Critical Theory. The core of this programme is a moral account of the basic right of justification that humans owe to one another as rational beings. This account is put to work by Forst in articulating - both historically and philosophically - the contexts and form of justice and of toleration. The result is a powerful theoretical framework within which to address issues such as transnational justice and multicultural toleration. In this volume, Forst sets out his ideas in an extended essay, which is responded to be influential interlocutors including: Andrea Sangiovanni, Amy Allen, Kevin Olson, Anthony Laden, Eva Erman and Simon Caney. The volume concludes with Forst's response to his interlocutors.